Hubungan Pengetahuan Ibu terhadap Penggunaan KB Suntik 1 Bulan di PMB Tri Utami Sari S.SiT Manyaran Semarang - Rina Maya Sari; Nella Vallen; Qomariyah Qomariyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
According to data collected from Midwifery Clinician Tri Utami Sari S.SiT Manyaran Semarang in 2022, injectable contraceptive users ranked first when compared to those using pills, condoms, IUDs, and implants. However, the use of 1-month injections is more common than 3-month injections. One of the factors is that the Fertile Spouse knowledge about 3 months of injectable contraception is still low, and the lack of support of the husband. This matter means that the use of 3 months of injective contraception is still small, approximately 300 of the 1240 participants. This cross-sectional study determined the correlation between a mother's knowledge and the use of a one-month injectable contraception. The study's population included a woman of fertile age who received a 1-month injectable contraception at the Midwifery Clinician Tri Utami Sari, S.SiT Manyaran. The researcher used a purposive sampling technique to gather a sample of 50 respondents. The Spearman rank correlation test found a p-value of less than 0.029, indicating no correlation between mother knowledge and one-month injectable contraception at Midwifery Clinician Tri Utami Sari S.SiT Semarang in the year 2023.